A complete thermo-electro-viscoelastic characterization of dielectric elastomers, Part II: Continuum modeling approach. (December 2021) - Mehnert, Markus; Hossain, Mokarram; Steinmann, Paul
Abstract: A comprehensive experimental study performed under a combination of thermo-electro-mechanical loads applied to a widely used electro-active polymer, is presented in the Part I of this work (Mehnert et al., 2021). Soft polymeric materials, used as base materials in electro-active polymers, are highly susceptible to temperature changes. Hence, thermal influences on their behavior have to be investigated precisely. Constitutive modeling and numerical simulation of electro-active polymers are active fields of current research. However, on the one hand, their experimental study under complex loading conditions is non-trivial. On the other hand, very few constitutive modeling approaches meet with experimental data obtained from thermo-electro-mechanical loading conditions. In this contribution, we aim to develop a thermo-electro-mechanically coupled model, which will closely replicate the response of an electro-active polymer investigated under a combination of thermal, electric and mechanical loads. Once the model is calibrated with the experimental data described in Part I of this contribution, it is validated with a different set of data, which shows excellent agreement with experimental findings.